2010
DOI: 10.1038/aps.2009.196
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin attenuates oxygen-glucose deprivation-induced injury by inhibiting oxidative stress-mediated 5-lipoxygenase activation in PC12 cells

Abstract: Aim: To determine whether the flavonoid baicalin attenuates oxygen-glucose deprivation (OGD)-induced injury by inhibiting oxidative stress-mediated 5-lipoxygenase (5-LOX) activation in PC12 cells. Methods: The effects of baicalin and the 5-LOX inhibitor zileuton on the changes induced by OGD/recovery or H 2 O 2 (an exogenous reactive oxygen species [ROS]) in green fluorescent protein-5-LOX-transfected PC12 cells were compared. Results: Both baicalin and zileuton attenuated OGD/recovery-and H 2 O 2 -induced inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Together with the neuroprotective effects of baicalin reported by others [7,11,12,19,21,30,31], this study provides further supportive evidence for the potential use of baicalin as a therapeutic agent to reduce A␤-induced neuronal cytotoxicity. It is possible that baicalin may be beneficial to prevent or treat AD acting through the aforementioned mechanisms, however, further in vivo studies are needed to determine whether baicalin or its metabolites can indeed be transported across the blood brain barrier to reach brain tissue and accumulate up to a level for performing such functions, as the existing evidence of baicalin absorption and tissue distribution data published to date for baicalin are inconclusive [3,13,18,30,33].…”
supporting
confidence: 84%
“…Together with the neuroprotective effects of baicalin reported by others [7,11,12,19,21,30,31], this study provides further supportive evidence for the potential use of baicalin as a therapeutic agent to reduce A␤-induced neuronal cytotoxicity. It is possible that baicalin may be beneficial to prevent or treat AD acting through the aforementioned mechanisms, however, further in vivo studies are needed to determine whether baicalin or its metabolites can indeed be transported across the blood brain barrier to reach brain tissue and accumulate up to a level for performing such functions, as the existing evidence of baicalin absorption and tissue distribution data published to date for baicalin are inconclusive [3,13,18,30,33].…”
supporting
confidence: 84%
“…35 It was recently reported that zileuton, another 5-LOX inhibitor with the same mechanism of action as BWB70C, does not suppress 5-LOX translocation to the nuclear envelope after oxygenglucose deprivation. 23,36 This is considered to provide reasonable explanation on the reason why BWB70C could not inhibit the 5-LOX translocation in our experiments. Therefore, these results suggest that concussion-induced 5-LOX activation in hippocampal astrocytes is associated with the appearance of depressive-like behavior.…”
Section: -Lipoxygenase Inhibition Prevented Concussion-induced Depresupporting
confidence: 62%
“…It can acquire neuron-like properties when exposed to nerve growth factor (NGF) [12] . Therefore, it is widely used as an in vitro model of cerebral ischemia/reperfusion [13,14] . Intracellular free calcium concentration ([Ca 2+ ] i ) and mitochondrial membrane potential (MMP) are important indicators to reflect cell injury.…”
Section: Introductionmentioning
confidence: 99%